Konsep Muamalah Dalam Bisnis Islam - Rasyid, Muh. Haras; Badwi, Ahmad (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2023)
One aspect that exists in Islamic teachings apart from aqidah and worship, is the muamalah aspect. For this reason, this paper will explore how the application of the concept of muamalah in Islamic business is exemplified from the Qur'an and hadith and several Islamic scholars' ijtihad related to today's modern business developments. Interaction between fellow human beings as the basic meaning of muamalah is a sunnatullah that cannot be avoided, especially in business matters. In this regard, to bridge business interactions between one person and another so that no party is harmed, the concept of muamalah which emphasizes the application of Islamic principles or values to anyone who carries out business activities is very necessary to be present in it.